2011
DOI: 10.1111/j.1468-1331.2011.03589.x
|View full text |Cite
|
Sign up to set email alerts
|

Pantothenate kinase‐associated neurodegeneration in Korea: recurrent R440P mutation in PANK2 and outcome of deep brain stimulation

Abstract: The c.1319G>C (p.R440P) mutation appears to be a founder genotype among Korean patients with PKAN. Furthermore, this study provides additional data for the recent international effort to evaluate the efficacy of pallidal DBS in the treatment of patients with PKAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Several other case reports also suggested that GPi-DBS could offer a therapeutic alternative for dystonia due to various focal brain lesions and inherited metabolic or genetic disorders. There is evidence to suggest that GPi-DBS may be effective in patients with PANK2 mutations (average motor improvement of 30%, although with marked variability) 129 135 134 137. Anecdotal reports also indicate that GPi-DBS could be useful in patients with dystonia secondary to GM1 gangliosidosis,150 mitochondrial disorder with striatal necrosis,151 Lesch–Nyhan disease138 145 144 152 and X-linked parkinsonism 153.…”
Section: Literature Analysis According To the Expected Outcomementioning
confidence: 99%
“…Several other case reports also suggested that GPi-DBS could offer a therapeutic alternative for dystonia due to various focal brain lesions and inherited metabolic or genetic disorders. There is evidence to suggest that GPi-DBS may be effective in patients with PANK2 mutations (average motor improvement of 30%, although with marked variability) 129 135 134 137. Anecdotal reports also indicate that GPi-DBS could be useful in patients with dystonia secondary to GM1 gangliosidosis,150 mitochondrial disorder with striatal necrosis,151 Lesch–Nyhan disease138 145 144 152 and X-linked parkinsonism 153.…”
Section: Literature Analysis According To the Expected Outcomementioning
confidence: 99%
“…This has prompted neurosurgical treatment attempts, such as stereotactic brain lesions [4,5], and, more recently, deep brain stimulation (DBS) surgery of the internal globus pallidus (GPi) [6-8] following reported success in the management of other hyperkinetic movement disorders [9-12]. However, only single case or small series have been reported heterogeneously and in the short term, which likely bias the results towards favourable outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The disease usually continues for 10-12 years, but some reports describe patients who survived for 30 years 12,14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the toxin was performed bilaterally in the gastrocnemius and soleus muscles in an attempt to reduce the dystonia in lower limbs. The bilateral pallidal deep brain stimulation also has been studied in treatment of patients with PKAN, with outcome favorable in the management of dystonia 15,17 .…”
Section: Discussionmentioning
confidence: 99%